2013
DOI: 10.1038/jhg.2013.24
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix remodeling genes polymorphisms and risk of chronic bronchitis and recurrent pneumonia in children

Abstract: We investigated the association of matrix metalloproteinases, the disintegrin and metalloprotease 33 and the tissue and serum inhibitors of proteinase gene polymorphisms with severe chronic respiratory diseases in Tatar children. We analyzed the case-control data sample from a total of 592 Tatar individuals, consisting of 119 children with chronic bronchitis, 138 with recurrent pneumonia and 335 control children residing in Ufa (Russia). The percentage of heterozygous genotype for the MMP9 (2660A>G) was higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
3
2
Order By: Relevance
“…indicating that the (–82) G allele associates with a reduced risk of COPD. The results of the present study also disagree with those of Korytina et al . who found a significant association between the (–82) A/G variant and increased risk of chronic bronchitis.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…indicating that the (–82) G allele associates with a reduced risk of COPD. The results of the present study also disagree with those of Korytina et al . who found a significant association between the (–82) A/G variant and increased risk of chronic bronchitis.…”
Section: Discussioncontrasting
confidence: 99%
“…and Tacheva et al30 indicating that the (-82) G allele associates with a reduced risk of COPD. The results of the present study also disagree with those of Korytina et al31 who found a significant association between the (-82) A/G variant and increased risk of chronic bronchitis. Likewise, data from studies by Haq et al32 and Arja et al33 showed an association between the (-82) A/357 A haplotype and the risk of developing COPD.…”
contrasting
confidence: 99%
“…Other MMPs also increased in the liver in response to carbon tetrachloride (CCl 4 ) administration, relating to inflammatory reactions [ 39 ], as well as APAP treatment, which were associated with hepatocellular damage and hepatic microcirculatory dysfunction [ 40 ]. Moreover, MMP12 haplotype may play a critical role in susceptibility to severe airway and lung injury in children with chronic bronchitis and recurrent pneumonia [ 41 ]. Therefore, we inferred that increased susceptibility to AILI in the rats with innately lower expression of Mmp12 might be the result of lacking tissue repair and remodeling ability to APAP-induced tissue damages.…”
Section: Discussionmentioning
confidence: 99%
“…TIMP3 is located on chro mosome 22 at site 22q12.1 q13.2; the (-1296T>C) polymorphisms in the gene promoter is thought to affect the level of TIMP3 transcription [13]. It was reported that TIMP3 contributes to the resolution of acute inflammatory damage to lung tissue [41]; the data from our previous studies suggested that TIMP3 locus was associated with COPD and with lingering childhood pneumonia [15,42].…”
Section: Discussionmentioning
confidence: 93%